Интертекстуальный анализ: Принципы и границы (Хроника конференции в Санкт-Пeтербургском государственном университете, 21–22 апреля 2016 года) [Intertextual Analysis: Principles and Limits. Conference overview ] - Dvinyatin, Fyodor; Leonenko, Semyon (Slavica Revalensia, 2016)
This overview is a detailed description of 29 scholarly papers presented at the conference on intertextual analysis at the St. Petersburg State University.